Augmenting THerapeutic Effectiveness Through Novel Analytics (ATHENA) - A Public and Private Partnership Project Funded by the Flemish Government (VLAIO)...32nd Medical Informatics Europe Conference (MIE2022), 27-30 May, 2022, Nice, France. - PETSOPHONSAKUL, Ploingarm; PIRMANI, Ashkan; BROUWER, Edward DE; AKAND, Murat; BOTERMANS, Wouter; DER AA, Frank VAN; VERMEESCH, Joris Robert; OFFNER, Fritz; WUYTS, Roel; MOREAU, Yves; MAES, Ingrid; BLOCKX, Ines; et al. (Studies in Health Technology & Informatics, 2022)
The complexity and heterogeneity of cancers leads to variable responses of patients to treatments and interventions. Developing models that accurately predict patient’s care pathways using prognostic and predictive biomarkers is increasingly important in both clinical practice and scientific research. The main objective of the ATHENA project is to: (1) accelerate data driven precision medicine for two use cases – bladder cancer and multiple myeloma, (2) apply distributed and privacy-preserving analytical methods/ algorithms to stratify patients (decision support), (3) help healthcare professionals deliver earlier and better targeted treatments, and (4) explore care pathway automations and improve outcomes for each patient. Challenges associated with data sharing and integration will be addressed and an appropriate federated data ecosystem will be created, enabling an interoperable foundation for data exchange, analysis and interpretation. By combining multidisciplinary expertise and tackling knowledge gaps in ATHENA, we propose a novel federated privacy preserving platform for oncology research.